Is the Effect of Environmental Attitudes on Behavior Driven Solely by Unobserved Heterogeneity? - Henrik Kenneth Andersen; Jochen Mayerl (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2022)
A~large body of research exists investigating the link between environmental attitudes and behavior. Many empirical studies have found modest positive effects, suggesting that attitudes toward the environment might indeed influence environmental behavior. However, most of the previous empirical work is cross-sectional and correlational in nature. This means that the issue of the causal effect of environmental attitudes on behavior is far from settled, and that the relationships observed in the past may be due to unobserved confounders. In a~panel study using six waves of the GESIS Panel Survey, we examine the individual-level effect of changes in one's attitudes on changes in different forms of environmental behavior. We use fixed effects panel regression within the structural equation modeling framework to control for unobserved time-invariant confounders, while also tackling other methodological challenges. We find that environmental attitudes have no effect on behavior after controlling for unobserved confounders. However, there is a~robust effect of attitudes on willingness to sacrifice. This suggests that creating more positive attitudes might make individuals more willing to accept sacrifices for environmental protection.
Keywords: 300; Attitudes and behavior; Willingness to pay/sacrifice; Panel analysis; Fixed effects; Structural equation modeling; Einstellungen und Verhalten; Opferbereitschaft; Panelanalyse; Strukturgleichungsmodelle